1979
DOI: 10.1111/j.1471-4159.1979.tb11706.x
|View full text |Cite
|
Sign up to set email alerts
|

STABILITY OF SYNAPTOSOMAL GABA LEVELS AND THEIR USE IN DETERMINING THE IN VIVO EFFECTS OF DRUGS: CONVULSANT AGENTS

Abstract: —The stability of the GABA content of synaptosomal‐enriched fractions was evaluated by two approaches. Firstly, the addition of 10−3m‐aminooxyacetic acid to the homogenizing medium totally inhibited the GABA‐degrading enzyme in the fractions but did not affect the GABA levels. This indicated that GABA was not being metabolized during the normal preparation of the synaptosomal‐enriched fraction. Secondly, when synaptosomal‐enriched fractions were re‐fractionated by discontinuous density gradient centrifugation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 21 publications
1
33
1
Order By: Relevance
“…1 could be used as a model to monitor drug-induced changes in GABA levels of nerve endings in the intact animal. Conspicuously, the finding that GABA levels increase during synaptosome preparation from rat brain regions without inclusion of 3-MP is in contrast with previous experiments by Wood et al (1979) using whole brains of mice for isolation of synaptosomes. In fact, these authors concluded from their experiments that GABA was not being metabolized during synaptosome preparation.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…1 could be used as a model to monitor drug-induced changes in GABA levels of nerve endings in the intact animal. Conspicuously, the finding that GABA levels increase during synaptosome preparation from rat brain regions without inclusion of 3-MP is in contrast with previous experiments by Wood et al (1979) using whole brains of mice for isolation of synaptosomes. In fact, these authors concluded from their experiments that GABA was not being metabolized during synaptosome preparation.…”
Section: Discussioncontrasting
confidence: 82%
“…Both drugs were studied in doses and times of administration previously found to result in about the same anticonvulsant effect against electroconvulsions in mice (LSscher, 1980). Although data obtained after subcellular fractionation may not accurately reflect the situation in the intact animal, previous studies with synaptosomes isolated from the whole brain of mice have indicated that valid information about in vivo alterations in nerve ending GABA levels can be obtained provided the data are analyzed carefully with respect to the possible occurrence of changes taking place during dissection, homogenization and fractionation of the tissue (cf., Wood et al, 1979;L~scher, 1981 a). Various control experiments in this respect have been carried out also for the synaptosomal model used in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…For interpretation of low CSF GABA levels in patients with epilepsy, recent experimental studies in dogs are of interest, which suggested that CSF GABA reflects turnover and release of GABA rather than its steady-state concentration in the brain (Loscher, 1982a). In fact, in many pharmacologically induced seizure states it is not the overall brain GABA level that is critical, but rather the relative availability of newly synthesized GABA (Wood et al, 1979b). In line with these considerations, the level of GABA in CSF of dogs was found to be positively correlated with the seizure threshold of the animals, i.e., dogs with low CSF GABA level had a high seizure excitability and vice versa (Loscher, 19826).…”
Section: Discussionmentioning
confidence: 97%
“…The decrease of GABA-ergic axon terminals at sites of experimental epileptic foci [9] and the induction of grand mal seizures after the experimental reduction of GABA levels in the brain [12] provide evidence in support of this role. Moreover, the GABA content of the CSF of epileptic patients was found to be low [11].…”
Section: Discussionmentioning
confidence: 98%